Health Biometrics: Ready to be a Smart Internet Technology? - Beekhuyzen, Jenine; Hellens, Liisa von; Siedle, Mark; Topor, Rodney; Stevens, Stella (Malaysian Journal of Computer Science, 2004)
Health informatics is increasingly of interest due to its potential in making our health care systems safer. The term ‘health or medical informatics’ refers to the “application of information technologies to optimise information management within all aspects of health care delivery" [1]. A research project has been initiated to explore the effectiveness of hospital clinicians and their professional group by developing tools to support electronic wireless access to medical literature, patient records and hospital databases. PDAs and other portable devices are considered as technologies that enable such access, but their suitability for clinicians depends on a range of organisational and technical issues including privacy and security of the systems. This paper introduces a selection of different technologies including signature recognition and a range of fingerprint scanning technologies designed for authentication and authorisation and critically evaluates their merits in accessing the health care systems.